(untitled) (Journal of Hama University, 2022)
The current research aimed to identify the extent to which teachers of the first cycle of basic education use the problem-centered learning strategy in teaching social studies in schools affiliated with the Hama Education Directorate. To achieve these goals, the research tool was applied, which is a questionnaire of teachers’ opinions, consisting of (36) items, distributed over three areas, (the role of the teacher, the role of the student, and the educational tasks presented), The sample also consisted of (155) male and female teachers from all teachers of the first cycle of basic education in the Directorate of Education of the city of Hama during their work in the second semester of the academic year 2020/2021 AD. The results of the research showed that the extent to which teachers use this strategy is medium, as it was found that there is no statistically significant difference between the mean scores of the sample members according to the variables of gender and experience and there was a statistically significant difference between the average scores of the groups due to the variable of training courses, and the differences were in favor of the group (more than 3 courses ) compared to the rest of the groups, and there were differences in favor of a group (from 1-3 courses) compared to a group (I did not follow any course), and there was no statistically significant difference between the mean scores of my groups (from 1-3 courses) and (more than 3 courses).for the first and second domains, and there is no statistically significant difference between the mean scores of my groups (1-3 courses) and (I did not follow any course) for the first and third domains. The research recommended the necessity of emphasizing the practice of the ideas of the learning strategy centered on the constructivist problem in the social studies education system by teachers, and their keenness to provide constructive classroom environments.